First Farmers in South India: The role of internal processes and external influences in the emergence and transformation of south India's earliest settled societies - Nicole Boivin, Dorian Fuller, Ravi Korisettar & Michael Petraglia (Pradghara (Journal of the Uttar Pradesh State Archaeology Department) 2007, 2007)
The Neolithic period in the south Deccan plateau of south India seems to have begun sometime in the 3rd millennium BC. It is therefore not one of the world's earliest Neolithic transitions, nor indeed the earliest Neolithic culture in South Asia. Nonetheless, the Southern Neolithic, as it is known in India, is of significant interest to Neolithic scholars worldwide because it appears in many significant ways to represent a largely indigenous transformation. This paper will explore the evidence for both internal processes and external influences in the genesis and subsequent transformation of Neolithic society in south India. It will in particular draw on recent studies at the site of Sanganakallu-Kupgal in the Bellary District of Karnataka, as well a larger-scale archaeobotanical project in the south Deccan plateau, in order to examine patterns of exchange, production and ritual in the Neolithic and Megalithic periods in south India